Aktivitas Antioksidan Kulit, Kitin dan Kitosan Teripang Pasir (Holothuria scabra) - Tyarani Dehwie; Sumarto Sumarto; Dahlia Dahlia (Agricultural Faculty, 2021)
Sea cucumber (H. scabra) has bioactive compounds that are useful as antioxidant. Antioxidant is chemical compound that can donate one or more electrons to free radical. Free radical is reactive compound that have unpaired electrons in the outer shell so it need antioxidant to stabilize. This study aims to determine the content of bioactive compounds and the antioxidant activity on the skin, chitin and chitosan of H. scabra. The analysis parameters observed were bioactive compounds and the antioxidant activity. The results showed that the phytochemical components in skin hexane extract were alkaloids, flavonoids, saponins and steroids/triterpenoids. Chitin contained alkaloids, flavonoids, and saponins. Chitosan contained alkaloid compounds, flavonoids and saponins. IC50 of skin hexane extract and chitin were 1445.05 ppm and 620.07 ppm respectively and included in the very low category. IC50 of chitosan was 235.37 ppm and included in the moderate category. Chitosan had the highest antioxidant activity.